Osun State approved budget for 1992: including budget speech - Osun State of Nigeria (Nigeria : TAA Printing and Publishing Company, 1992)
This was christened, 'the foundation budget' in realization of the commitment of the Social Democratic Party, to the creation of a new social order in the country, particularly in the state
osc 05/04/2019
Arch
Keywords: Budget; Nigeria